PENILAIAN KEPUASAN MAHASISWA PADA PELAKSANAAN PEMBELAJARAN MELALUI IMPORTANCE PERFORMANCE ANALYSIS DI AKADEMI PARIWISATA INDONESIA JAKARTA - Nova Eviana (Eduturisma, 2016)
This study aims to measure student satisfaction towards the implementation of the learning process in AKPINDO. The learning components include as follows (1). lecturers, (2). facilities and infrastructure management, and (3). the procedure, which are developed into 13 indicators. Respondents are 100 of AKPINDO’s students who are determined based on the Slovin‘s formula, using simple random technique. Data analysis technique use Importance Performace Analysis with assistance of SPSS ver. 20. The results show that of the three dimensions measured, the highest satisfaction is the implementation of the procedure, while the lowest is the management of facilities and infrastructure.